2021
DOI: 10.1063/5.0038812
|View full text |Cite
|
Sign up to set email alerts
|

Effective structure of a system with continuous polydispersity

Abstract: In a system of N particles, with continuous size polydispersity, there exists an N(N − 1) number of partial structure factors, making it analytically less tractable. A common practice is to treat the system as an effective one component system, which is known to exhibit an artificial softening of the structure. The aim of this study is to describe the system in terms of M pseudospecies such that we can avoid this artificial softening but, at the same time, have a value of M ≪ N. We use potential energy and pai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…1 This onset temperature can also be identified as the temperature where the pair part of the excess entropy becomes less than the total excess entropy of the system. 2,3 Below Tonset, the temperature dependence of the dynamics can be described reasonably well by the so-called mode-coupling theory (MCT), which predicts a power-law divergence of the relaxation times at a dynamic transition temperature Tc. 4 However, experimental and numerical studies found [5][6][7][8][9][10] that the relaxation time does not diverge at Tc as predicted by the MCT but instead shows a smooth crossover to weaker temperature dependence.…”
Section: Introductionmentioning
confidence: 94%
“…1 This onset temperature can also be identified as the temperature where the pair part of the excess entropy becomes less than the total excess entropy of the system. 2,3 Below Tonset, the temperature dependence of the dynamics can be described reasonably well by the so-called mode-coupling theory (MCT), which predicts a power-law divergence of the relaxation times at a dynamic transition temperature Tc. 4 However, experimental and numerical studies found [5][6][7][8][9][10] that the relaxation time does not diverge at Tc as predicted by the MCT but instead shows a smooth crossover to weaker temperature dependence.…”
Section: Introductionmentioning
confidence: 94%
“…2 indicate a population of LFS that is distinct from the rest of the liquid, it would be interesting to understand more precisely if the higherdimensional structural descriptor can be decomposed into a large number of structural states (or modes). A related problem arises in studies of polydisperse colloidal suspensions, when looking for an effective description of structure and thermodynamics in terms of a discrete number of families of particles 77,78 . Identifying the number of distinct modes of a high-dimensional distribution is a delicate task in unsupervised learning 42 and even well-established tests used in cluster analysis (such as the Bayesian information criterion, used for instance in Ref.…”
Section: B Modality and Temperature Dependence Of Structural Heteroge...mentioning
confidence: 99%